Initial Development of the Intersectionality Pedagogy Scale - Thompson, Jenae D.; Frazier, Walter L. (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
In this study, an instrument was developed to measure an instructor’s value and incorporation of intersectionality theory in the classroom. Through a Delphi study, a list of items was devised, and then a pilot study was conducted to collect responses from 161 participants. The result is the development of the Intersectionality Pedagogy Scale, a 23-item scale with a single factor that measures intersectionality pedagogy. The implications for this study will be discussed, along with recommendations for further research.